Green preparation and supercapacitive behaviors of calcium carbide derived porous carbon based on solvent-free mechanochemical route. (July 2022) - Yang, Juan; Chen, Yulian; Peng, Jiao; Zeng, Junqing; Li, Guang; Chang, Baobao; Shen, Yongqiang; Guo, Xiaowei; Chen, Gairong; Wang, Xianyou; Zheng, Liping
Abstract: Carbide-derived carbon (CDC) as a late-model type of porous carbon material has become a potential electrode material for supercapacitor. However, the preparation methods of Cl2 etching and electrochemical etching are environmentally unfriendly and extremely difficult for large-scale production. Thus, exploring a simple and environmentally friendly synthetic method of CDC materials is very imperative. In this work, calcium carbide derived porous carbon (CCDPC) is successfully synthesized through solvent-free mechanochemical reaction. The results show that the CCDPC is a kind of micro-mesoporous combination material with layered structure, partial graphite-like structure and high specific surface area of 525.3 cm 2 g −1 . It has been found that the as-prepared electrode possesses a better electrochemical performance in 1 M KOH electrolyte, and the specific capacitance reaches up to 205.4 F g −1 at current density of 0.5 A g −1 . Furthermore, the assembled symmetric supercapacitor displays a high cycle stability, the capacitance retention still remains 93% after 30, 000 cycles. Therefore, the preparation strategy of CCDPC with excellent electrochemical properties through a simple mechanochemical reaction provides an innovative synthetic idea for the preparation of calcium carbide derived carbon materials for the application of supercapacitors. Highlights: The CCDPC was synthesized by solvent-free mechanochemical method of CaC2 and Na2 CO3 . The CCDPC shows the layered micro-mesoporous structure, high SSA and partial graphitization. The specific capacitance of the CCDPC electrode is superior to other carbide-derived carbon materials. The CCDPC SC exhibits remarkable cycling stability of 93% after 30, 000 times charge-discharge under 2.0 A g -1 . This work provides an innovative synthetic idea for the preparation of calcium carbide derived carbon materials.